2013
DOI: 10.1373/clinchem.2012.190686
|View full text |Cite
|
Sign up to set email alerts
|

Direct Characterization of Motion-Dependent Parameters of Sperm in a Microfluidic Device: Proof of Principle

Abstract: BACKGROUND: Semen analysis is essential for evaluating male infertility. Besides sperm concentration, other properties, such as motility and morphology, are critical indicators in assessing sperm quality. Nevertheless, rapid and complete assessment of these measures still presents considerable difficulty and involves a range of complex issues. Here we present a microfluidic device capable of quantifying a range of properties of human sperm via the resistive pulse technique (RPT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A number of microfluidic devices have been developed for male factor infertility screening and can be used to distinguish motile sperm and measure sperm motility, motile sperm concentration, and motile sperm count (13,14). Although these devices have many advantages, they also have some limitations.…”
Section: Future Possibilitiesmentioning
confidence: 99%
“…A number of microfluidic devices have been developed for male factor infertility screening and can be used to distinguish motile sperm and measure sperm motility, motile sperm concentration, and motile sperm count (13,14). Although these devices have many advantages, they also have some limitations.…”
Section: Future Possibilitiesmentioning
confidence: 99%
“…21 Microfluidics enable complete control of the physical and chemical environments surrounding the investigated biological sample and have been used in many biological applications including in vitro fertilization, [22][23][24] sperm sorting, 23,25,26 and sperm analysis. 27,28 The first of these two studies, by Tung et al, 12 reported rheotactic behavior of bull sperm in grooved microchannels mimicking the cervix walls in the female reproductive system. It was found that these grooves help sperm cells migrate against fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little attention has been focused on single sperm analysis and the vast majority of studies measure sperm samples as a whole and obtain population averages. 25,26 Some studies have emerged where single sperm cells have been trapped using dielectrophoretic forces 27 and optical forces. 28 Although these systems are valuable, they lack HTP capabilities and require sophisticated equipment or fabrication steps.…”
Section: Introductionmentioning
confidence: 99%